The Existence and Transmission of the Meaning of Pocung Songs as Intangible Cultural Heritage in the Digital Era - Faijah, Ayesa Siti; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2024)
Tembang Pocung, as part of the Javanese macapat tradition, faces extinction due to digital culture penetration and value shifts among younger generations. This study aims to: (1) analyze the semiotic layers of Pocung songs structurally and culturally; (2) identify factors influencing the existence of Pocung songs in the digital era; and (3) formulate a digital literacy-based cultural transmission model to sustain Pocung songs. The research employs a qualitative descriptive approach with content analysis of Pocung song texts combined with document study. Roland Barthes' semiotics framework is applied to examine denotative, connotative, and mythological meanings. Results show that Pocung songs contain three layers of meaning: (1) eschatological meaning reflecting Javanese death philosophy; (2) pedagogical meaning as a medium for internalizing values; and (3) socio-ritualistic meaning within community contexts. The primary factors in its declining existence are low digital cultural literacy and the absence of formal integration in the educational curriculum. An interactive digital platform-based transmission model is proposed as a revitalization solution relevant to Generation Z's cultural consumption patterns.